Y and Ni Co-Doped BaZrO3 as a Proton-Conducting Solid Oxide Fuel Cell Electrolyte Exhibiting Superior Power Performance. Issue 14 (1st January 2015) - Shafi, Shahid P.; Bi, Lei; Boulfrad, Samir; Traversa, Enrico
Abstract : The fabrication of anode supported single cells based on BaZr0.8 Y0.2 O3-δ (BZY20) electrolyte is challenging due to its poor sinteractive nature. The acceleration of shrinkage behavior, improved sinterability and larger grain size were achieved by the partial substitution of Zr with Ni in the BZY perovskite. Phase pure Ni-doped BZY powders of nominal compositions BaZr0.8-x Y0.2 Nix O3-δ were synthesized up to x = 0.04 using a wet chemical combustion synthesis route. BaZr0.76 Y0.2 Ni0.04 O3-δ (BZYNi04) exhibited adequate total conductivity and the open circuit voltage (OCV) values measured on the BZYNi04 pellet suggested lack of significant electronic contribution. The improved sinterability of BZYNi04 assisted the ease in film fabrication and this coupled with the application of an anode functional layer and a suitable cathode, PrBaCo2 O5+δ (PBCO), resulted in a superior fuel cell power performance. With humidified hydrogen and static air as the fuel and oxidant, respectively, a peak power density value of 428 and 240 mW cm −2 was obtained at 700 and 600°C, respectively.